Searching for a new yardstick: the league of nations, intellectual cooperation and the Soviet challenge - Schacht, Anastassiya (Intellectual cooperation at the League of Nations, 2025)
“As the product and the continuing instrument of social revolution, the Soviet system requires a new and different yardstick for measuring its various features”.
Gesehen am 08.01.2026